Β‐carotene treatment alters the cellular death process in oxidative stress‐induced K562 cells. (1st February 2017) - Akçakaya, Handan; Tok, Sabiha; Dal, Fulya; Cinar, Suzan Adin; Nurten, Rustem
Abstract: Oxidizing agents (e.g., H2 O2 ) cause structural and functional disruptions of molecules by affecting lipids, proteins, and nucleic acids. As a result, cellular mechanisms related to disrupted macro molecules are affected and cell death is induced. Oxidative damage can be prevented at a certain point by antioxidants or the damage can be reversed. In this work, we studied the cellular response against oxidative stress induced by H2 O2 and antioxidant–oxidant (β‐carotene–H2 O2 ) interactions in terms of time, concentration, and treatment method (pre‐, co‐, and post) in K562 cells. We showed that co‐ or post‐treatment with β‐carotene did not protect cells from the damage of oxidative stress furthermore co‐ and post‐β‐carotene‐treated oxidative stress induced cells showed similar results with only H2 O2 treated cells. However, β‐carotene pre‐treatment prevented oxidative damage induced by H2 O2 at concentrations lower than 1, 000 μM compared with only H2 O2 ‐treated and co‐ and post‐β‐carotene‐treated oxidative stress‐induced cells in terms of studied cellular parameters (mitochondrial membrane potential [Δψm ], cell cycle and apoptosis). Prevention effect of β‐carotene pre‐treatment was lost at concentrations higher than 1, 000 μM H2 O2 (2–10 mM). These findings suggest that β‐carotene pre‐treatment alters the effects of oxidative damage induced by H2 O2 and cell death processes in K562 cells.